Low-cost floating solar still for developing countries: Prototyping and heat-mass transfer analysis - Faiz Akbar Raihananda (Elsevier, 2021)
Floating solar still is a suitable technology for remote or rural coastal area applications. The device should be made of low-cost materials available locally to provide more access to the broader community. However, the low-cost materials usually do not have the best physical properties, decreasing the overall solar still performance. This work demonstrated a low-cost floating solar still prototype entirely made of locally available materials. To further understand the influence of different parameters on the solar still performance and guide the prototyping process, we also performed the system's heat and mass transfer analysis. Our experimental results indicate a high absorber temperature (59.5 °C), even on a cloudy day. Our model also fits the temperature measurement reasonably. However, the recorded overall efficiency still suffers mainly due to the collection system, which decreases the overall performance; an example of a practical challenge, which is often overlooked but plays a crucial role in increasing the readiness level of the prototype.